Identification and Quantitative Characterization of Point Bars in Subsurface Meander-River Belt, Taking Chengdao Oilfield in Bohai Bay Basin as an Example - Yang, Bin; Zhang, Liqiang; Sun, Zhifeng; Yan, Yiming (Frontiers in Earth Science, 2022)
Reservoir architecture is an important basis for studying the sedimentary evolution of underground reservoirs and the distribution of remaining oil. Taking meander-river reservoir of Guantao Formation in Chengdao Oilfield as an example, characteristics of the evolution of subsurface meander-belt deposits were studied by seismic sedimentology. Seismic lithology is performed using -90° phase wavelet and frequency fusions; seismic geomorphology is conducted on seismic stratal slices. Six meandering belts were defined in the target layer, and the sediment at the bottom is characterized by the transformation from “braided” river to “meandering” river. The width of meander-river belt has no correlation with the maximum thickness of meander-river belt. But it has obvious negative correlation differences in the minimum thickness of meander–river belt. With the increase of width of the meander-river belt, the minimum thickness of the drilled meander-river belt decreases as a whole. The forward model based on the shape of point bar reveals the seismic architecture characteristics formed by the superposition of sand bodies at different positions of point bars. According to these characteristics, the point bars in the meandering zone can be explained. In the Ng33, Ng42, and Ng45 sub-layers of the study area, the corresponding meander-belt widths where the point bar (or point bar connecting body) cannot be effectively identified by well logging and seismic data, are, respectively, 800, 800, and 500 m. At the same time, when the width of the meander belt is greater than 1000 m, three or more than three point bars (or point bar connecting body) can be basically identified in the meander belt. The width of the point bar segments in the meander belt of the three main sub-layers is mostly 300–400 m, and the maximum width of the point bar segments is about 550 m, while the scale of point bars in Ng45 sub-layer meander belt is relatively small. The quantitative characteristics of point bar debris and the determined location of SBM and SIA sand bodies provide limited and valuable data support for the formation and simulation of underground meandering rivers, which are also useful for the model of the target reservoir.